2021
DOI: 10.1186/s12916-021-02148-5
|View full text |Cite
|
Sign up to set email alerts
|

m6A regulator expression profile predicts the prognosis, benefit of adjuvant chemotherapy, and response to anti-PD-1 immunotherapy in patients with small-cell lung cancer

Abstract: Background Small cell lung cancer (SCLC) is lethal and possesses limited therapeutic options. Platinum-based chemotherapy—with or without immune checkpoint inhibitors (anti-PDs)—is the current first-line therapy for SCLCs; however, its associated outcomes are heterogeneous. N6-methyladenosine (m6A) is a novel and decisive factor in tumour progression, chemotherapy resistance, and immunotherapy response. However, m6A modification in SCLC remains poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In addition, kaempferol can inhibit the occurrence and development of prostate cancer by inhibiting the expression of Ki67 [ 31 ]. Kaempferol and TGF- β receptor (ALK5) binding inhibits the phosphorylation and translocation of Smad2 and reduces the expression of Smad4, thus inhibiting the proliferation, migration, and invasion of tumor cells [ 32 ]. To date, chemotherapy is still an important treatment for patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, kaempferol can inhibit the occurrence and development of prostate cancer by inhibiting the expression of Ki67 [ 31 ]. Kaempferol and TGF- β receptor (ALK5) binding inhibits the phosphorylation and translocation of Smad2 and reduces the expression of Smad4, thus inhibiting the proliferation, migration, and invasion of tumor cells [ 32 ]. To date, chemotherapy is still an important treatment for patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly regulated by the m6A methylation regulator ( Chen et al, 2019 ; Liu et al, 2019 ). Previous studies have focused on the relationship between m6A and the occurrence and development of LUAD ( Li et al, 2022 ; Ma et al, 2022 ; Qian et al, 2021 ), or the relationship between the m6A regulatory factor and chemotherapy resistance of small cell lung cancer ( Zhang et al, 2021a ; Zhang et al, 2021b ). Some studies have also found that the m6A regulatory factor is closely related to LUAD resistance to erlotinib ( Li K et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…111 In another study that assessed tumors from 231 patients with LS-SCLC who were treated with chemoradiotherapy, CDK4 and GATA6 expression as well as EGFR-activating mutations were prognostic for poorer OS (HR, 2.18; HR, 2.39; HR, 2.26). 160 Additionally, Zhang et al 109 created a prognostic signature based on N 6 -methyladenosine (m 6 A), an epigenetic modification involved in tumorigenesis and immune function. Among 265 patients with LS-SCLC, those with a high m6A score had decreased OS (HR, 5.19; 95% CI, 2.75 to 9.77; P < .001), a finding that was validated in two independent cohorts.…”
Section: Recommendationsmentioning
confidence: 99%